GREENWASHING: INFLUENCE ON THE DEVELOPMENT AND SUSTAINABILITY OF TOURISM IN INDONESIA - Khil Wailmi; Mahrinasari MS; Ayi Ahadiyat (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine (1) the influence of greenwashing on the image of tourism in Indonesia; (2) the influence of greenwashing on green consumer confusion in Indonesia, and (3) the influence of greenwashing on the development and sustainability of Indonesian tourism. This research is qualitative-descriptive research. The results of this research show that (1) Greenwashing practices have a negative effect on the image of tourism. Greenwashing practices represent inappropriate environmentally friendly claims that can create wrong perceptions about tourism and damage market demand; (2) Greenwashing practices negatively influence green consumer confusion. Tourists are confused when tourism destinations under the auspices of tourism stakeholders make environmentally friendly claims which turn out to be just marketing tactics, this slows down the movement towards sustainable consumption in the tourism industry; and (3) Greenwashing practices negatively influence the development and sustainability of tourism in Indonesia. The greenwashing phenomenon has been found in several cases in Indonesia, for example the practice of greenwashing by drinking water companies as a tourism requirement which claims to be environmentally friendly but does not match the facts on the ground. This can hinder the development and sustainability of Indonesian tourism.